MOLECULAR-BEAM INFRARED-ABSORPTION STUDIES OF RARE-GAS OCS COMPLEXES - Hayman, G; Hodge, J; Howard, B; Muenter, J; Dyke, T (1985)
Resolved vibration-rotation spectra for Ne·OCS, Ar·OCS and Kr·OCS in the ν3 region of the OCS monomer have been obtained by absorption spectroscopy of pulsed molecular beams. Rotational constants for the upper and lower vibrational states and the band origins were determined, and effective structures for these molecules were calculated. © 1985.